Smartphone's Sound Testing in Home Setting - Ozimek, Marcin (Journal of Computer Sciences Institute, 2016)
Quality of sound is one of the most important factors while choosing the perfect smartphone model. This article concerns about domestic sound testing of smartphones. Both ways of examining and the equipment used for it are discussed. These tests have been performed on popular models of smarphones: Galaxy S6, iPhone 6S and Lumia 950 to collect recent data and to achieve the essential aim: establishing the fact which model is the best in terms of sound processing.